2015
DOI: 10.1159/000434679
|View full text |Cite
|
Sign up to set email alerts
|

Parabromophenacyl Bromide Inhibits Subepithelial Fibrosis by Reducing TGF-β<sub>1</sub> in a Chronic Mouse Model of Allergic Asthma

Abstract: Background: Our previous study showed that parabromophenacyl bromide (PBPB) inhibits the features of allergic airway inflammation and airway hyperresponsiveness (AHR). However, its effect on airway remodeling, e.g. subepithelial fibrosis in a chronic allergic asthma model, was not investigated. We examined this issue in this study. Methods: PBPB was administered to mice with an induced chronic asthmatic condition. AHR was estimated at the end of the experiment, followed by euthanasia. Lung sections were stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In Th cells, GCs may restore Th1/Th2 balance by altering the secretion of various cytokines, which induce Th cell differentiation [5]. In our study, we confirmed that DEX decreased airway responsiveness and inflammation [25], and we also found that DEX could inhibit Th2 cytokine production and increase Th1 cytokine production in OVA-sensitized mice. A novel finding in our study is that DEX enhanced T-bet expression but inhibited GATA3 expression through the Notch1 (NICD1)-RBPj pathway, which in turn induced changes in the Th1 and Th2 phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…In Th cells, GCs may restore Th1/Th2 balance by altering the secretion of various cytokines, which induce Th cell differentiation [5]. In our study, we confirmed that DEX decreased airway responsiveness and inflammation [25], and we also found that DEX could inhibit Th2 cytokine production and increase Th1 cytokine production in OVA-sensitized mice. A novel finding in our study is that DEX enhanced T-bet expression but inhibited GATA3 expression through the Notch1 (NICD1)-RBPj pathway, which in turn induced changes in the Th1 and Th2 phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, it has been shown in a mouse model of P. aeruginosa infection that AZ increases arginase-1 expression as well as the activation of latent TGFβ 1 , consistent with polarisation to M2 macrophages. Consequently, the fibronectin concentration has been increased, and a fibrotic process is intensified [32,33] . This fact may partially explain the relatively short period of beneficial effect of AZ in the treatment of CF lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among all cytokines and chemokines that can be produced by bronchial epithelial cells, TGF-b1 was recognized as an important factor inducing proliferation of subepithelial fibroblasts and as a driving force of cell differentiation and activation. Increased levels of TGF-b1 have been reported in bronchoalveolar lavage fluids and biopsy specimens of asthma patients (21,22), and TGF-b1 expression correlated with the degree of subepithelial fibrosis (23,24). In healthy humans, the concentration of circulating TGF-b ranges from 0.26 to 20 ng/ml (25)(26)(27), whereas in asthma patients, the circulating TGF-b concentration ranges from 38 to 215 ng/ml (28,29).…”
Section: Discussionmentioning
confidence: 98%